1990
DOI: 10.1111/j.1365-2621.1990.tb06751.x
|View full text |Cite
|
Sign up to set email alerts
|

Flavor Characteristics of Forage‐ and Grain‐Fed Beef as Influenced by Phospholipid and Fatty Acid Compositional Differences

Abstract: Neutral lipid (NL) and phospholipid (PL) fractions and their corresnonding fattv acid CFA) nrofiles from the L. dorsi of Angus-Hereford hkifers 6=2?) we& cc&pared as a function of forage grazing (FG) and time in the feedlot after grazing (DIF) on pasture. There were no differences in total PL content or FA composition of the individual PL as influenced by initial FG. As DIF increased, there was an increase in PL concentration and significant changes in the FA composition of the total PL and several of the indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
3
7

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(71 citation statements)
references
References 35 publications
2
59
3
7
Order By: Relevance
“…Diets high in grains, for example corn, can increase the ω6 and polyunsaturated acids changing the flavor and smell. Grass based diets increase ω3 in the meat, which contributes to healthy meat (Larick & Turner, 1990). There were interactions between sex-type and time on feed for C12:0, C14:1C9, C15:1, C17:0, C18:1C9, C18:1T16, C18:2C9C12 acids, monounsaturated, polyunsaturated and ω6 (Table 6).…”
Section: Resultsmentioning
confidence: 99%
“…Diets high in grains, for example corn, can increase the ω6 and polyunsaturated acids changing the flavor and smell. Grass based diets increase ω3 in the meat, which contributes to healthy meat (Larick & Turner, 1990). There were interactions between sex-type and time on feed for C12:0, C14:1C9, C15:1, C17:0, C18:1C9, C18:1T16, C18:2C9C12 acids, monounsaturated, polyunsaturated and ω6 (Table 6).…”
Section: Resultsmentioning
confidence: 99%
“…About half of the total lipids from the SR membrane measured in this study are phospholipids (Table 3). Larick and Turner (1990) and Noci et al (2005) reported that PUFA, especially 18:2, are predominately associated with the phospholipid fraction. Therefore, the greater content of PUFA in SR membrane than muscle tissue was expected.…”
Section: Sr Membrane Fatty Acidsmentioning
confidence: 99%
“…Isto se deve ao alto conteúdo de AG ω-3 (C18: 3) presente nas forragens, enquanto que os grãos são normalmente ricos em AG ω-6 (C18: 2) (LARICK; TURNER, 1990;RAES et al, 2003;WOOD et al, 2003). Em geral, os AG da gordura intramuscular da carne bovina são compostos por aproximadamente 44% de saturados, 5% de cadeia ímpar, 45% de monoinsaturados e 5% de polinsaturados (DUCKETT, 2002).…”
Section: Perfil De áCidos Graxos Qualidade Da Carcaça E Da Carneunclassified
“…O metabolismo ruminal modifica o perfil dos ácidos graxos da gordura da dieta disponíveis para absorção intestinal e a biohidrogenação no rúmen influencia a digestibilidade da gordura, sendo o principal fator determinante do perfil de ácidos graxos saturados constituintes da gordura corporal dos ruminantes (FRENCH et al, 2000;JENKINS, 1993;LARICK;TURNER, 1990;PALMQUIST, 1996).…”
Section: Perfil De áCidos Graxos Qualidade Da Carcaça E Da Carneunclassified
See 1 more Smart Citation